Investigation into the anticancer activity of biosynthesized zinc oxide nanoparticles incorporating 6-gingerols - Noor Hayder Mohammed Al-Hamadani; Vahid Pouresmaeil; Mahshid Sharbatiyan; Masoud Homayouni Tabrizi (Cellular, Molecular and Biomedical Reports)
Ginger is a popular spice, and 6-gingerol (6-Gin) is a bioactive phenolic compound. The compound 6-Gin exhibits certain drawbacks, including poor solubility in water and sensitivity to temperature, pH, and oxygen. To overcome these challenges, a novel green method has been developed to produce zinc oxide nanoparticles (ZnO-NPs) modified with chitosan and folate, which can effectively deliver 6-Gin (6-Gin-CZF-NPs) and enhance its anticancer properties. The nanoparticles were initially synthesized and subsequently surface-modified. Their physicochemical properties were assessed using various methods. The size of the 6-Gin-CZF-NPs was measured at 110.66 nm, exhibiting a smooth surface and a spherical shape. The surface potential of the nanoparticles was reported to be +29 mV, and the drug encapsulation efficiency was 86.9%. The antioxidant properties and anticancer effects of the 6-Gin-CZF-NPs were evaluated. The cytotoxic effects of the 6-Gin-CZF-NPs on breast, stomach, and colon cancer cells were compared to those on HFF cells, yielding IC50 values of 94.4, 180.5, and 369.2 μg/mL, respectively. Results from DAPI staining and flow cytometry indicated that in the treated groups, apoptosis increased with higher concentrations, leading to an accumulation of treated cells in the SubG1 phase. The increase in Caspase 3, 8, and 9 further confirmed the pro-apoptotic activity of the 6-Gin-CZF-NPs. This inhibition of cancer cells occurs through the induction of apoptosis via both intrinsic and extrinsic pathways. The IC50 values for ABTS and DPPH assays were 197.7 and 475.3 µg/mL, respectively. The results regarding antioxidant activity, cytotoxicity, and apoptosis of these newly prepared nanoparticles confirm their anticancer efficacy, particularly against breast cancer cells.